The relationship between human resource management practices, organizational commitment, career concern, job stress and turnover intention - Nawaz, Muhammad Shahid (2016)
Any academic institution cannot survive and perform well without competent and committed academic staff. Therefore, it is important to address the issue of faculty turnover. It has been argued that faculty dissatisfaction with existing human resource practices such as no provision of equitable salary, performance appraisal, training and development, job stress and lack of career growth practices could lead to turnover. Hence, the focus of this study is to investigate the relationship between human resource practices, focusing specifically on examining the effect of salary, performance appraisal, training and development, and career growth (career goal progress, professional ability development, promotion speed, and remuneration growth) and employee’s turnover intention. This study also investigates the mediating role of organizational commitment on these relationships, as well as the moderating role of career concern and job stress on the relationships between organizational commitment and turnover intention. Using a cross sectional survey technique, this study gathers data from a sample of 270 full time faculty members of private universities in Pakistan. The Partial Least Square (PLS) two step path modeling was used to test the direct and indirect hypotheses. The results indicate that salary and performance appraisal are significantly and negatively related to turnover intention. Besides, it was found that out of four dimensions of career growth, only promotion speed and remuneration growth, have significant direct relationship with turnover intention. Nonetheless, with regard to mediated relationships, it was found that organizational commitment mediates the relationships between performance appraisal as well three dimensions of career growth (career goal progress, promotion speed, remuneration growth) and turnover intention. The results verify that these relationships are mediated by organizational commitment except salary. Nevertheless, the results also show that career concern plays an important role in moderating the relationship between organizational commitment and turnover intention. This finding suggests that to reduce turnover intention amongst employees, organizations must realize that the impact of organizational commitment in reducing turnover intention is enhanced whenever the employees are concerned about their career growth. Hence, employees’ career development should also be the concern of organizations.